How to deal with a CAPEX-bias: Fixed-OPEX-CAPEX-share (FOCS) - Carlotta von Bebenburg; Gert Brunekreeft; Anton Burger (Jacobs University Bremen, Bremen Energy Research (BER), 2022)
In recent years, the OPEX-CAPEX-incentive-bias (short: CAPEX-bias) received renewed attention in regulatory practice. A CAPEX-bias occurs when the OPEX solution is the more efficient approach, but regulation sets distorted incentives to choose the CAPEX solution. This paper presents a promising approach to address the CAPEX-bias: the fixedOPEX-CAPEX-share (FOCS). With FOCS, all expenses, whether for capital goods (CAPEX) or operational measures (OPEX), are treated as TOTEX. A fixed portion, the capitalisation rate of this TOTEX, is then "capitalised" (quasi-CAPEX) and the remaining portion is directly expensed as quasi-OPEX ("pay-as-you-go"). Because all costs are treated equally, any distortion of behaviour that would arise because of the different treatment of costs, disappears. Similarly, the regulatory effort of scrutinising cost classification is no longer required. The paper also discusses practical implementation issues and first international experience.
Keywords: D42; K23; L51; 330; monopoly regulation; CAPEX-bias; FOCS